A Randomized, Double‐Blind, Placebo‐Controlled Trial of Duloxetine for the Treatment of Pain in Patients with Multiple Sclerosis. Issue 8 (24th October 2013) - Vollmer, Timothy L.; Robinson, Michael J.; Risser, Richard C.; Malcolm, Sandra K.
Abstract Background Patients with multiple sclerosis (MS) often report neuropathic pain (NP‐MS). The purpose of this study was to assess the efficacy and tolerability of duloxetine as treatment for NP‐MS. Methods In this study, 239 adults with NP‐MS (duloxetine = 118, placebo = 121) were randomized to duloxetine 60 mg (30 mg for 1 week, then 60 mg for 5 weeks) or placebo once daily for a 6‐week acute therapy phase, followed by a 12‐week open‐label extension phase (duloxetine 30 to 120 mg/day). Eligible patients had MS for ≥ 1 year and a score ≥ 4 on daily average pain intensity (API) ratings for ≥ 4 of 7 days immediately before randomization. Patients rated API daily on an 11‐point numeric scale (0 [no pain] to 10 [worst possible pain]) in an electronic diary. The primary efficacy measure, change in weekly API ratings, was analyzed longitudinally with a mixed‐model repeated‐measures analysis. Completion, reasons for discontinuation, and treatment‐emergent adverse event incidence were compared by Fisher's exact test. Results Duloxetine‐treated patients had statistically greater mean improvement in API vs. placebo at Week 6 (−1.83 vs. −1.07, P = 0.001). Treatment completion did not significantly differ between groups. Discontinuation due to adverse events was statistically greater for duloxetine vs. placebo (13.6% vs. 4.1%, P = 0.012). Decreased appetite was reported significantly more often by duloxetine‐treated patients (5.9% vs. 0%, P = 0.007). Conclusions This study found analgesic efficacy of duloxetine for NP‐MS. Duloxetine is not approved for treatment of this condition. The duloxetine safety profile of this study was consistent with the known profile in other patient populations.